Coastal inundation risk assessment using multi-mission satellite altimeter and digital elevation models - Nur Fadila Khalid, 1990-, author; Ami Hassan Md. Din, supervisor; Kamaludin Mohd. Omar, supervisor; Mohd. Faisal Abdul Khanan; Fakulti Alam Bina dan Ukur (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Sarjana Falsafah (Kejuruteraan Geomatik)) - Universiti Teknologi Malaysia, 2018